2017
DOI: 10.1038/gt.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CNS targeting in adult mice by intrathecal infusion of single-stranded AAV9-GFP for gene therapy of neurological disorders

Abstract: Adeno-associated virus (AAV) gene therapy constitutes a powerful tool for the treatment of neurodegenerative diseases. While AAVs are generally administered systemically to newborns in preclinical studies of neurological disorders, in adults the maturity of the blood-brain barrier (BBB) must be considered when selecting the route of administration. Delivery of AAVs into the cerebrospinal fluid (CSF) represents an attractive approach to target the central nervous system (CNS) and bypass the BBB. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 47 publications
6
54
0
Order By: Relevance
“…A single IT injection of AAV.hGAA also led to neurologic and cardiac improvements in Pompe disease (Hordeaux et al, 2017), while similar central and peripheral benefits could be demonstrated after infusion of AAV9, AAVrh.10, and AAV.Olig001 in young Krabbe disease mice (10-11 days old; Karumuthil-Melethil et al, 2016). Overall, the transduction efficacy appears to be rather equivalent in adult mice when comparing different routes of administration in the CSF (Bey et al, 2017), but infusion of AAV9 in the cisterna magna or in the lateral ventricle has been shown to be far more potent at transducing the brain and spinal cord of cynomolgus macaques or dogs as compared with IT injection by lumbar puncture (Hinderer et al, 2018a). Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015).…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 77%
“…A single IT injection of AAV.hGAA also led to neurologic and cardiac improvements in Pompe disease (Hordeaux et al, 2017), while similar central and peripheral benefits could be demonstrated after infusion of AAV9, AAVrh.10, and AAV.Olig001 in young Krabbe disease mice (10-11 days old; Karumuthil-Melethil et al, 2016). Overall, the transduction efficacy appears to be rather equivalent in adult mice when comparing different routes of administration in the CSF (Bey et al, 2017), but infusion of AAV9 in the cisterna magna or in the lateral ventricle has been shown to be far more potent at transducing the brain and spinal cord of cynomolgus macaques or dogs as compared with IT injection by lumbar puncture (Hinderer et al, 2018a). Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015).…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 77%
“…AAV2/9 was significantly more efficient than AAV2/rh10 regarding the transduction rate at the injection site (83% vs 32% respectively on average). This high transduction rate is clearly correlated to the injection protocol as an intrathecal injection of the same vectors of newborn or adult mice resulted in the transduction of a large amount of neurons and glial cells [4,22,23,53] but no mSC in sciatic nerves. While we cannot rule out a transduction of mSC in nerve roots close to the spinal cord after intrathecal injection, intra nerve injection appears as the most efficient way to transduce these cells in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…We previously demonstrated that a single administration of an adeno-associated virus serotype 9 and 10 (AAV9 and AAVrh10) expressing green fluorescent protein transgene (GFP) into the cerebrospinal fluid (CSF) leads to widespread GFP distribution into the brain, spinal cord and peripheral organs in rodent models. 24,25 We also demonstrated that intra-CSF administration of an AAV9 and AAVrh10 expressing hGAA therapeutic transgene in GAA-KO 6 neo /6 neo Pompe mice, allowed significant decrease of glycogen storage into the brain, spinal cord and cardiac muscle, at the histological and molecular levels, with higher efficiency using serotype 9. 26 Significant functional neurologic correction was obtained starting at four months and hypertrophic cardiomyopathy correction was observed at twelve months in AAV9-treated animals.…”
Section: Introductionmentioning
confidence: 73%